Amelioration of Behavioural, Biochemical, and Neurophysiological Deficits by Combination of Monosodium Glutamate with Resveratrol/Alpha-Lipoic Acid/Coenzyme Q10 in Rat Model of Cisplatin-Induced Peripheral Neuropathy - Naini Bhadri; Tejaswi Sanji; Hariprasad Madakasira Guggilla; Rema Razdan (The Scientific World Journal)
Cisplatin or cis-diamminedichloroplatinum (II) (CDDP) is a cytotoxic chemotherapeutic agent with dose-dependent peripheral neuropathy as a foremost side effect characterised by ataxia, pain, and sensory impairment. Cumulative drug therapy of CDDP is known to produce severe oxidative damage. It mainly targets and accumulates in dorsal root ganglia that in turn cause damage resulting in secondary nerve fibre axonopathy. In the present study, we investigated the neuroprotective effect of the combination of monosodium glutamate (MSG) with three individual antioxidants, that is, resveratrol, alpha-lipoic acid (ALA), and coenzyme Q10 (CoQ10), in cisplatin (2 mg/kg i.p. twice weekly) induced peripheral neuropathy in rats. After 8 weeks of treatment the degree of neuroprotection was determined by measuring behavioral and electrophysiological properties and sciatic nerve lipid peroxidation, as well as glutathione and catalase levels. The results suggested that pretreatment with the combination of MSG (500 mg/kg/day po) with resveratrol (10 mg/kg/day i.p.) or ALA (20 mg/kg/day i.p.) or CoQ10 (10 mg/kg weekly thrice i.p.) exhibited neuroprotective effect. The maximum neuroprotection of MSG was observed in the combination with resveratrol.